PROBLEMS OF INCREASING THE SOCIAL AND POLITICAL ACTIVITY OF WOMEN IN THE SYSTEM OF STATE POWER (Scientific journal of the Fergana State University, 2026)
The article considers one of the important problems of our time - increasing the social activity of members of society, their active participation in democratic reforms and socio-political processes implemented in society, the importance of the role of women leaders in the management process, the positive impact of their activities on the social activity of both women and youth, as well as the specific role of women in society, their activities are often associated with the functions they perform in the management system, and this aspect, as a specific feature of the activities of women leaders, sometimes creates difficulties or, conversely, relative ease in their activities. Socialization of women, creation of the necessary conditions for the realization of their aspirations and dreams in socio-political processes, their objectification are important both for women and for the public administration system. The ability of women to express themselves, reveal their knowledge, experience and potential, have the opportunity for their further development and implementation serves the positive dynamics of the public administration system and the interests of the population. It is analyzed that such socio-political processes further enhance the political culture and activity of women.